Teachers’ and Parents’ Perspectives on the Feasibility of a Preschool-Based Behavioral Intervention to Prevent Obesity: An Embedded Qualitative Study within ToyBox Study Malaysia - Julia Ai Cheng, Lee; Whye Lian, Cheah; Gordon, Anchang; Noor Hafizah, Yatiman; Abim, M.; Ruzita, Abdul Talib; Denise, Koh; Sue, Reeves; Carolyn, Summerbell; Cecilia, Essau; Bee Koon, Poh; Edward Leigh, Gibson (Springer, 2022)
The aim of this qualitative study, an embedded component of ToyBox Study Malaysia (TSM), was to elicit the perspectives of teachers and parents regarding the implementation of TSM. TSM is a preschool-based behavioral intervention program aimed at improving healthy energy balance-related behaviors among young children attending preschools. The qualitative study adopted a descriptive-interpretive methodology, and triangulated data collected through semi-structured focus groups with artifacts collected. The setting involved rural and metropolitan preschools in Sarawak and Peninsular Malaysia, respectively. In Sarawak, 11 teachers and 20 parents from six intervention preschools participated in this study. In Peninsular Malaysia, 14 preschool teachers and seven assistant teachers representing all 15 intervention preschools participated in the study. Data were analyzed thematically and four overarching themes were identifed: impact of TSM on the children’s knowledge and practices of healthy energy balance-related behaviors; spheres of infuence upon the children’s energy balance-related behaviors; constraints and afordances related to the implementation of TSM; and prospective sustainability of TSM. The triangulation of data from teachers, parents, and the artifacts related to TSM enabled the corroboration of evidence to support the themes identifed. This study provides evidence on the reciprocal interactions between the teachers and parents who played key roles in facilitating behavioral change in the children, and the children who, in turn, served as change agents beyond the preschool. Furthermore, the mediational tools such as the TSM crockery and availability of healthy food and water led to the reported behavioral changes at both rural and metropolitan settings.